2019
DOI: 10.17645/mac.v7i2.1817
|View full text |Cite
|
Sign up to set email alerts
|

Board Games as Interview Tools: Creating a Safe Space for Unaccompanied Refugee Children

Abstract: Since the emergence of the new sociology of childhood in the late 1980s, there has been an increasing expectation to engage children actively and to take their views seriously throughout the research process. This is even more important when it comes to unaccompanied refugee children, whose voice is seldom heard. In this article the author builds upon her project of exploring unaccompanied refugee children’s lived media experiences and argues that—in order to have meaningful results and to create safe spaces f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…Newcomer children may not fully understand the research purpose, methods, or potential risks and benefits (White et al, 2010). McBrien and Day (2012) noted the risk of participants giving consent out of a desire to please researchers, and Neag (2019) reported that some with refugee experience have difficulty distinguishing between researchers and service providers.…”
Section: Access To Newcomer Children's Voices Through Participatory Vmentioning
confidence: 99%
“…Newcomer children may not fully understand the research purpose, methods, or potential risks and benefits (White et al, 2010). McBrien and Day (2012) noted the risk of participants giving consent out of a desire to please researchers, and Neag (2019) reported that some with refugee experience have difficulty distinguishing between researchers and service providers.…”
Section: Access To Newcomer Children's Voices Through Participatory Vmentioning
confidence: 99%
“…The empirical research which we will discuss below is part of a larger two-year project that explored how unaccompanied young refugees used social media and digital technology in four different European countries (Sweden, the Netherlands, Italy, the UK). Though this article solely focuses on research gathered in the second ethnographic phase, it is worth mentioning that in the first phase, a total of 56 unaccompanied refugee youth were interviewed using a specially designed board game (Neag, 2019). The second phase consisted of a month-long social media ethnography (Postill and Pink, 2012) of Facebook profiles belonging to 16 unaccompanied young refugees (11 living in Sweden, 5 in Italy; 12 males, 4 females) who agreed to take part in both research phases.…”
Section: Facebook Profiles Of Refugee Youth: a Social Media Ethnograpmentioning
confidence: 99%
“…Ta'lim al-'Arabiyyah : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 4 (2), 2020 In language learning, games and songs are used as a medium for language learning (Saepurrohman & Nurhayati, 2019). The use of games in education aims to make learning interactive and exciting, as (Neag, 2019) games are interactive learning media that can make students active and quickly understand the material. Meanwhile, (Hakim, 2018) the results of his research show that songs can motivate learners' learning and make learning engaging, fun, and make the material easier to understand.…”
Section: Stories For Advancementioning
confidence: 99%